A study on the illuminated manuscripts from the parchment to the digital library online: report on a project со-financed by the European Social Founds - Cantone, Valentina (Actual Problems of Theory and History of Art, 2012)
The Menologium Marcianus Graecus 360 (696) of Venice shows a repertory of decorations useful to investigate the symbolic relations between illumination and architecture. Even if it was realized in Constantinople around the middle of the 10th century, in the same milieu of well known manuscripts, it was never considered before by the art historians. For its importance, the manuscript will be published in a monograph and entirely digitalized thanks to the resources off ered by the European Social Founds. It will be available online in the website http://www.nuovabibliotecamanoscritta.it/index.html
Keywords: Byzantine illuminated manuscripts; Menologium; Biblioteca Marciana in Venice; ornament; architectural decoration; symbolic of decorative elements